2014
DOI: 10.5688/ajpe78237
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Exercises to Teach Clinically Relevant Chemistry of Antibiotics

Abstract: Objectives. To design, implement, and evaluate student performance on clinically relevant chemical and spectral laboratory exercises on antibiotics. Design. In the first of 2 exercises, second-year pharmacy students enrolled in an integrated laboratory sequence course studied the aqueous stability of ß-lactam antibiotics using a spectral visual approach. In a second exercise, students studied the tendency of tetracycline, rifamycins, and fluoroquinolones to form insoluble chelate complexes (turbidity) with pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This trend is supported by an increase in publications addressing curricular integration in pharmacy during the past decade. 3,5,[10][11][12][13][14][15][16][17][18][19][20][21] It is surprising that only 50% of the schools indicated that experiential education is used to address curricular integration. The low percentage might be a result of lack of awareness by respondents on how experiential education is conducted at their schools as there were at least 20 schools with conflicting data.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is supported by an increase in publications addressing curricular integration in pharmacy during the past decade. 3,5,[10][11][12][13][14][15][16][17][18][19][20][21] It is surprising that only 50% of the schools indicated that experiential education is used to address curricular integration. The low percentage might be a result of lack of awareness by respondents on how experiential education is conducted at their schools as there were at least 20 schools with conflicting data.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating a laboratory activity can be worthwhile to address the gaps. This was shown by [44] found that laboratory exercises on spectral visual approaches increased student retention of the concepts. In addition, in the study of [45], they introduced an online laboratory exercise for their physics topic which was positively accepted by the students.…”
Section: Environmental Awareness In Terms Of Practicementioning
confidence: 89%
“…Many faculty members took advantage of the introductions of skills laboratories to address key educational outcomes as part of their courses [2][3][4][5][6] and to improve required skills. At Creighton University, the pharmacy skills laboratory (PSL) course sequence was implemented in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…For pharmaceutical sciences faculty members, the PSL offered a vehicle to demonstrate the importance of their discipline to the comprehensive curriculum and to pharmacy practice. 2,6 We previously implemented several classroom-based strategies including treatment algorithms, 7 electronic integration of prerequisite content, 8 learning games, 9 and the structurally-based therapeutic evaluation (SBTE) concept 10 to help students appreciate the relevance of medicinal chemistry to pharmacy practice and to instill self-directed learning by students. 11,12 The PSL was intended to provide a unique venue with sufficient time to reinforce what was being taught in the classroom, to challenge students to integrate and apply what they had learned, and to increase their confidence in their ability to meet course objectives and perform (self-efficacy).…”
Section: Introductionmentioning
confidence: 99%